IMPLEMENTING AUTHENTIC AI ASSESSMENT IN TESOL: CHALLENGES AND RESEARCH DIRECTIONS - Dilnoza Usmanova (TADQIQOTLAR, 2025)
This article addresses the practical challenges of implementing authentic AI-enhanced language assessment in TESOL contexts. Drawing on a four-dimensional framework of authenticity, we identify key implementation barriers at technological, pedagogical, and institutional levels. We propose a research agenda to address these challenges  and  offer  practical  guidelines  for  TESOL  practitioners  navigating  the integration of AI assessment tools. The article concludes with recommendations for interdisciplinary  collaboration  between  language  educators,  AI  developers,  and assessment researchers.